(untitled) (Bangladesh Critical Care Journal, 2017)
Aim: This study aims to evaluate the safety of ultrasound guided emergency cannulation of internal jugular vein in coagulopathic adult patients. Methods: Adult subjects admitted in the intensive care unit, undergoing emergency cannulation of internal jugular vein under real time ultrasonographic guidance with platelet count less than 50,000/cu mm and/or international normalized ratio (INR) more than 1.5 were enrolled. Major and minor complications during the procedure were noted. Results: Internal jugular vein was successfully cannulated in all the patients. The mean INR of patients having minor complications (provided that platelet count > 50000) was found to be 3.07 with 95% confidence interval(CI) being 2.37-3.77. The mean platelet count of patients having minor complications (provided that the INR<1.5) was found to be 27428 with 95% CI being 19428-36000. There was a significant relationship between margin of safety and occurrence of minor complications (>7mm vs 7mm or less; p value 0.027). Number of attempts while performing internal jugular vein cannulation was associated with minor complications (mean 1.5 with CI 1.2-1.78 vs mean 1.08 with 95% CI 1.00-1.25; p value 0.023). No major complications were reported during the study regardless of platelet count, INR, margin of safety or number of attempts. Conclusions: Emergency cannulation of internal jugular vein may be safely performed in coagulopathic adult patients under real-time ultrasound guidance when performed by an experienced physician. Bangladesh Crit Care J September 2017; 5(2): 93-96